Analisis Pengaruh Harga Hijau terhadap Loyalitas Pelanggan Produk Ramah Lingkungan - Rahardian Mohamad Akbar Ario Hanung Prabandaru; Mirzam Arqy Ahmadi (Universitas 45 Surabaya, 2025)
Green economy and sustainable industries are experiencing rapid growth. This is driven by increasingly stringent environmental regulations and growing public awareness of sustainability’s importance. In response, companies are focusing on developing eco-friendly products and resource efficiency to meet high regulatory standards and meet consumer expectations regarding environmental impact.This study aims to investigate the impact of green pricing on customer loyalty, considering customer satisfaction as a mediating variable. A quantitative approach was employed, collecting primary data through questionnaires from 150 respondents. Analysis reveals significant positive effects of green pricing on customer satisfaction and satisfaction on loyalty. These findings provide strategic implications for companies to integrate green pricing into marketing strategies to enhance customer satisfaction and loyalty. Companies should integrate green pricing practices in marketing strategies to increase customer satisfaction and loyalty. This can be done by: (1) offering discounts or rebates for environmentally friendly products, (2) communicating the environmental benefits of these products, (3) developing loyalty programs that support environmental awareness, and (4) communicating and distorting the impact of green pricing on customer satisfaction and loyalty. In this way, companies can improve their brand image, expand market share, and support environmental sustainability.